Planejamento estratégico de uma instância de governança regional: estudo de caso da Adeturoeste - Francez, Simone Cristina (2020)
This study aimed to formulate actions for the implementation of strategic planning in the Regional Governance Instance - Adeturoeste (Tourism Development Agency of the Western Region of Paraná). The methodology used was a case study using CANVAS and SWOT Analysis tools. The information was collected through the participation of assemblies with the board and associates, in addition to exchanging emails and messages via WhatsApp, especially in meetings with the executive secretary. The results pointed out the weaknesses (weaknesses and threats) that exist in the organization, which must be treated as a priority, especially with regard to seeking an administrative headquarters with infrastructure and seeking new registrations in order to increase its financial resources. On the other hand, it was also observed that there is a wide range of opportunities to be explored and that they can provide improvements in the agency's performance and promote the development of tourism in the entire region. It is suggested that research be carried out in other Regional Governance Instances to compare different realities and monitor the implementation of the suggestions offered to Adetur.